Digital Emotional Dependency In Islamic Da'wah: A Psychospiritual Analysis Of Neurobiological And Behavioral Impacts - Oprimuriandy T.D. Putra; Akif Khilmiyah; Azam Syukur Rahmatullah; Husain Azhari (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study aims to explore the psychospiritual dimensions of Digital Emotional Dependence (DED) in the context of Islamic da'wah and communication, and analyze its impact on the effectiveness of Islamic educational technology and ethical engagement in religious digital platforms. The study uses a phenomenological approach with a systematic literature review of empirical research from 2010-2024 that examines the neurobiological, psychological, and spiritual aspects of digital dependency in religious communication. The analysis was conducted on the neurological dimensions (prefrontal cortex and amygdala activity), neurotransmitter mechanisms (dopamine and serotonin), and subjective experiences of spiritual emotional regulation in the context of digital da'wah. The findings show that DED in digital da'wah is correlated with decreased capacity for tafakkur (spiritual contemplation), impaired regulation of religious emotions, and fragmentation of spiritual experiences. Digital dependency creates dissonance between the consumption of religious content and the implementation of Islamic values, resulting in maladaptive coping mechanisms that hinder authentic spiritual transformation. Respondents showed increased impulsivity in religious digital interactions and decreased ability to deeply contemplate da'wah messages. Conclusion: A holistic intervention is needed that integrates Islamic digital literacy, dhikr and muraqabah-based spiritual practices, and a tawhid-based cognitive-behavioral approach to optimize digital religious communication and prevent counterproductive emotional dependence on Islamic spiritual goals.